2021
DOI: 10.2528/pierc21110202
|View full text |Cite
|
Sign up to set email alerts
|

Wideband Designs of Regular Shape Microstrip Antennas Using Modified Ground Plane

Abstract: Wideband designs of proximity fed regular shape microstrip antennas using bow-tie and H-shape ground plane profiles are proposed in the 1000 MHz frequency range. The modified ground plane alters the quality factor of the patch cavity which enhances the impedance bandwidth. In terms of the results obtained for the bandwidth and gain together, circular and square patches backed by bow-tie shape ground plane, followed by circular patch backed by H-shape ground plane yield optimum results. For substrate thickness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Also, details about the antenna working in terms of patch resonant modes and design methodology are not discussed. Wideband designs discussed in [26][27][28] do not provide a reduction in patch size or the frequency as bow-tie shape does not perturb the current distribution in the patch center where the maximum of modal current is present. Against the reported wideband configurations, proposed work explains a technique to yield wider BW supported with reduction in patch resonant mode frequency (patch area) on an electrically thinner substrate.…”
Section: Results Discussion and Comparative Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Also, details about the antenna working in terms of patch resonant modes and design methodology are not discussed. Wideband designs discussed in [26][27][28] do not provide a reduction in patch size or the frequency as bow-tie shape does not perturb the current distribution in the patch center where the maximum of modal current is present. Against the reported wideband configurations, proposed work explains a technique to yield wider BW supported with reduction in patch resonant mode frequency (patch area) on an electrically thinner substrate.…”
Section: Results Discussion and Comparative Analysismentioning
confidence: 99%
“…2(e), (f). In the bow-tie shape designs reported in [26][27][28], the reduction in patch fundamental mode frequency is not achieved. As against that in the proposed design, the presence of a rectangular slot before the realization of bow-tie shape of the ground increases perturbation in current vector lengths that reduces the resonance frequency.…”
Section: Rmsa Employing Slots Cut Bow-tie Shape Ground Plane Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Against this, the proposed MSA offers stable gain characteristics across the S 11 BW. In modified ground plane MSAs discussed in Deshmukh et al, 12 Poonam and Deshmukh, 15 and Deshmukh et al, 16 and in none of the reported work, a technique to reduce the antenna size, while providing a wider BW is being discussed. Against the reported wideband MSAs, the present study not just discusses another wideband configuration on thinner substrate but provides a simple technique that reduces the patch resonance frequency (size).…”
Section: Comparative Analysismentioning
confidence: 99%